Systems approaches to innovation in crop protection. A systematic literature review - Schut, Marc; Rodenburg, J.; Klerkx, Laurens; Ast, A. van; Bastiaans, L. (Elsevier, 2014)
The objective of this paper is to explore the extent to which systems approaches to innovation are reflected in the crop protection literature and how such approaches are used. A systematic literature review is conducted to study the relation between crop protection and systems approaches to innovation in 107 publications. The analysis of the crop protection literature demonstrates that only a small fraction is systems-oriented as compared to the bulk of publications with a technology-oriented approach. The analysis of agricultural innovations systems literature shows that, although crop protection is addressed, the potential of this systems approach remains largely unexplored for crop protection innovation. A large share of the publications included in this review focus on cropping or farming ‘systems’ while ‘innovation’ often equals the development, transfer, adoption and diffusion of crop protection technologies at farm level. There is relatively little attention for the institutional and political dimensions of crop protection and the interactions between farm, regional and national levels in crop protection systems. The traditional division of roles and responsibilities of researchers as innovators, extension personnel as disseminators, and farmers as end-users, is challenged only to a limited extent. The majority of publications discusses ways to optimise existing features of crop protection systems, without exploring more structural transformations that may be required to enhance the resilience of crop protection systems.